Towards a New Way of War: American Strategy and the Utility of Force - Sehili, Assia (Journal of Human Sciences, 2022)
The foundations of a typical American way of war that emerged out of a specific strategic culture were deeply challenged throughout American history by a succession of crises. The most significant of these was the failure of the American military intervention in Vietnam. This crisis produced crucial transformations that in turn engendered a new way of war. This new way of war, drawing upon the latest information and weaponry technology, allowed the USA to preserve its global status in the aftermath of the Cold War, but utterly failed to address the core concern of strategy that of giving war its effective political utility. This article attempts to evaluate the importance given in the USA to the understanding of military strategy on the light of internal and external variables and the extent to which this understanding reflects the significance given to the utility of military force as a continuation of politics.